Learn Azure serverless functions in a weekend. (Packt Publishing, 2023)
Serverless functions are a single-purpose, programmatic feature of serverless computing (cloud computing execution model). It helps execute code written in the language of your choice with Azure Functions, an event-driven computing experience. Scale on-demand and pay only for the time your code is executed. Available as a managed service in Azure and Azure Stack, the open-source functions runtime also works on multiple destinations, including Kubernetes, Azure IoT Edge, on-premises, and even in other clouds. You will start with learning Azure Serverless Functions from scratch in a stepwise manner. Then look at the basic concepts of serverless computing, event-driven application, Azure Functions, and Azure Service Bus. After that, you will look at Azure Serverless Functions' interaction with the database, Azure Service Bus, and queue bindings in Azure Serverless Functions. You will explore how to send emails and messages using Azure Functions. Additionally, you will delve into version control using GitHub Actions Workflow and learn about Azure Functions monitoring. Finally, you will have the opportunity to develop a transaction management system application with Azure Functions. By the end of this course, you will have learned Azure Serverless Computing concepts with Azure Functions. What You Will Learn Study serverless computing and event-driven application Look at Azure Serverless Functions' interaction with the database Learn Azure Service Bus and queue bindings in Azure Functions Send emails and messages with Azure Functions See the Azure Functions integrations with Azure Service Bus Develop a transaction management system with Azure Functions Audience This course is designed for cloud consultants who work on platform automation requirements or those who want to experience the power of Azure Serverless Computing. Azure IAAS and PAAS administrators, Azure/application developers, and cloud computing enthusiasts will also gain a lot from this course. To get the most out of this course, you should have some basic understanding of the command line (Win CMD/Unix Shell) that will help you quickly grasp the concepts, and Visual Studio Code installed on the laptop. About The Author Vijay Saini: Vijay Saini is an accomplished IT professional who brings a wealth of expertise to the table. With a diversified background across multiple domains, Vijay has proven himself a valuable asset to his current role as a leading cloud service provider. His strong focus on automation has resulted in significant cost savings for the business, making him a valuable asset to the team. Vijay is highly knowledgeable in the areas of Microsoft Azure, cloud technologies, DBMS, and Python, and is a specialist in automation using PowerShell. With a passion for teaching, Vijay has leveraged e-learning platforms to share his expertise with others, helping them develop their own skills and knowledge.